El cuerpo en las imágenes de los libros de texto de educación física: análisis de dos editoriales - Táboas País, María Inés; Rey Cao, Ana Isabel (KRONOS, 2007)
This article goal is to study about corporal pictures showed in mandatory Secondary Physical Education text books and check if there is any kind of relationship between certain body models and the type of moving pattern they are linked up with.A mainly descriptive study using inner elements analysis as major techniche is organizad. The sample is composed of 242 pictures (99 published in “Paidotribo” Publishers Secondary Education Physical Education text book and the other 143 in “Anaya” Publishers). First, an analysis instrument is developed for the images thar are object of this study, whose construction process consists on two show tests, two experts advice and the three observers triangle. Results show that white race youth males prevail in analyzed images. Also, the differences between the two publishers are clear. In Paidotribo book non white race males are associated with elite sport; on the other hand, female are associated with another type of activities.